E-learning theory and practice - Haythornthwaite, Caroline; Andrews, Richard 1953- (SAGE, 2011)
In 'E-learning Theory and Practice', the authors set out different perspectives on e-learning. The book deals with the social implications of e-learning, its transformative effects, and the social and technical interplay that supports and directs e-learning